Human monopoly - Abd Rahim, Ain Syahirah; Muhamamad, Nur Fatin Adila; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2017)
Human monopoly is one of the board game that involve player itself in this game. This game aim to help the autism sufferers an opportunities to communicate with others in non – verbal way, To combine a bunch of activities that appropriate for autistics children and to help ADHD sufferers to overcome focusing problem. Human monopoly is imitation from the monopoly board game. The difference is they using human player itself as a symbol. In each spot, they can choose either fate or chance only. Each fate or chance card is a flash card where there is instructions and activities in a short time. This board game encourage relationship between autism sufferers and other by using playgroup concept.